The Relationship between Knowledge, Attitudes and Behaviors of Hemodialysis Nurses Towards Preventing Risk of Catheter Infection Doube Lumen Tunneling at X Jakarta Hospital - Yuli Verawati; Lia Natalia (Indonesian Journal of Global Health Research, 2025)
Infection in Catheter Double Lumen (CDL) tunneling is a complication that often occurs in patients with hemodialysis.The prevention of infection in tunneling CDL can be achieved through nurses' possession of adequate knowledge, attitudes, and behaviors regarding the care of tunneling CDL access, as well as the provision of proper information to patients and families.The objective of this study is to ascertain the relationship between nurses' knowledge, attitudes, and behaviors regarding the prevention of infection in tunneling CDL at Hospital X Jakarta. The research method employed is quantitative, utilizing a descriptive correlation research design with a cross-sectional approach.The sample collection technique employed total sampling of 46 hemodialysis nurses. The results of univariate analysis indicated that the majority of respondents were female (93.5%), aged 31-40 years (47.8%), had a Diploma 3 education level (69.6%), exhibited good category knowledge (65.2%), good category attitude (65.2%), and good category behavior (69.6%). The results of Kendal's Tau B analysis demonstrated a relationship between nurses' knowledge and attitude regarding the prevention of CDL infection (p-value 0.014) and a relationship between nurses' behavior and the prevention of CDL infection (p-value 0.004). The knowledge, attitudes, and behaviors of nurses have been identified as a crucial component in the prevention of infection in the context of CDL tunneling. Hospitals are expected to implement training programs, disseminate Standard Operating Procedures on infection control in CDL, and conduct ongoing monitoring and evaluation to mitigate the risk of CDL infection.